Can ceding planning controls for major projects support metropolitan housing supply and diversity? The case of Sydney, Australia. (March 2021) - Gilbert, Catherine; Gurran, Nicole
Highlights: Analysed outcomes of a major planning reform designed to address local planning barriers to new housing development. The reform allowed for the approval of projects that significantly deviated from zoning and development control policies. Characteristics and outcomes of 80 applicable residential development applications analysed using mixed research methods. Found that high density infill housing that would not otherwise have been permissible was approved. Not all approved projects commenced and there was limited diversity of dwelling types or affordable housing. Abstract: Local land use planning policies and decision-making processes are often perceived as a barrier to new housing production, particularly higher density housing in established areas. In the context of wider debates about the impact of local regulatory planning on housing supply and diversity, this paper examines the outcomes of a policy experiment that was introduced in the Australian state of New South Wales (NSW), which is home to the Sydney metropolitan region, in 2005. The Major Projects reform enabled developers of large projects, including residential and mixed use projects to bypass local planning controls and to have their project approved by the Minister for Planning on a discretionary basis, in many instances, negating the need for formal land rezoning. Based on a detailed analysis of development applications that were determined under the Major Projects reform, we examine whether ceding local land use regulations enabled housing approvals above what would be permitted under local land use policy and whether approved dwellings supported key metropolitan housing and spatial development goals, including increased housing supply and diversity through urban consolidation. We find that the reform did result in housing approvals, particularly for higher density infill development, that would likely not have been permitted by local governments. However, by 2016, not all approved projects had commenced. Overall the results highlight the limitations of ceding power to the market to achieve housing supply and affordability goals.